VDJtools: Unifying Post-analysis of T Cell Receptor Repertoires - Shugay, Mikhail; Bagaev, Dmitriy V; Turchaninova, Maria A; Bolotin, Dmitriy A; Britanova, Olga V; Putintseva, Ekaterina V; Pogorelyy, Mikhail V; Nazarov, Vadim I; Zvyagin, Ivan V; Kirgizova, Vitalina I; Kirgizov, Kirill I; Skorobogatova, Elena V; et al. (PLoS computational biology, 2015)
Despite the growing number of immune repertoire sequencing studies, the field still lacks software for analysis and comprehension of this high-dimensional data. Here we report VDJtools, a complementary software suite that solves a wide range of T cell receptor (TCR) repertoires post-analysis tasks, provides a detailed tabular output and publication-ready graphics, and is built on top of a flexible API. Using TCR datasets for a large cohort of unrelated healthy donors, twins, and multiple sclerosis patients we demonstrate that VDJtools greatly facilitates the analysis and leads to sound biological conclusions. VDJtools software and documentation are available at https://github.com/mikessh/vdjtools.
Keywords: dospělí; shluková analýza; Cluster Analysis; Software; Humans; Hematopoietic Stem Cell Transplantation; Sequence Analysis, DNA; Computational Biology; mladý dospělý; software; transplantace hematopoetických kmenových buněk; Adult; výpočetní biologie; Adolescent; receptory antigenů T-buněk; roztroušená skleróza; Multiple Sclerosis; Twins; Receptors, Antigen, T-Cell; dvojčata; sekvenční analýza DNA; lidé; mladiství; dítě; Child; Young Adult